Some noise cancellation and prediction methods on the response probability distribution form for complicated sound wall systems with background noise - OHTA, M.; TAKAKI, N. (Archives of Acoustics, 2001)
In the actual situation of measuring an environmental noise, it is very often that only the resultant stochastic fluctuation contaminated by an additional noise of arbitrary distribution type can be observed. In this paper at first a noise cancellation for reasonably removing the effect of the above additional noise, especially in a whole probability distribution form, is derived theoretically in order to estimate only the undisturbed objective output response. Next, for the purpose of predicting a whole expression form of the output response probability of an acoustic system excited by an arbitrary stochastic input with the additional noise, a new stochastic signal processing method, reflecting the effect of the additional noise fluctuation, is proposed in a whole probability distribution form. The effectiveness of the proposed theoretical methods is experimentally confirmed too by applying them to the actual data measured in the complicated sound wall systems.